AB1367 Persistency with subcutaneous anti-TNF therapy for treatment of rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis patients. (23rd January 2014) - Tandon, N.; Haas, S.; Waters, H.C.; Olson, W.; Bolge, S.; Gunnarsson, C.
Abstract : Background: Rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) are chronic autoimmune diseases that result in destructive inflammation of the joints, as well as other organs. Golimumab, adalimumab, and etanercept are subcutaneous biologic therapies indicated for the treatment of moderately to severely active RA, PsA, and AS in adults. Objectives: To understand real world persistence in patients who receive golimumab, adalimumab and etanercept using administrative claims data. Methods: This study used the MarketScan® Research Database from Thomson Reuters. Patients were diagnosed with RA, PsA, or AS and aged ≥18 years at index date, with continuous enrollment for 6 months prior to and 364 days following the initial medication fill. Patients had ≥2 fills and a 28-31 day supply of study drug (golimumab, adalimumab, or etanercept) for all fills during the 365 day study period. Matches for golimumab patients were obtained using propensity score matching for a range of demographic characteristics and 1:1 matching for prior biologic experience. Duration of therapy was calculated as the minimum of (1) the number of days between the date of last dose within the study window and the date of first dose plus the days supply for the last dose; and (2) 365 days. Treatment persistence was defined as: (duration/365) × 100. Results: Prior to matching, there were significant differences between the golimumab, adalimumab, and etanercept cohorts in terms of age, gender, geographic region, previous biologic use, last biologic previous to the index biologic, primary diagnosis, and psoriasis comorbidity. Golimumab patients were older than adalimumab or etanercept patients (mean age =52.09 vs. 50.52 and 50.07, p=0.028) and more likely to be female (74.3% vs. 65.7% and 71.3%, p=0.002). Golimumab patients were also more likely to have previous biologic experience than adalimumab or etanercept patients (79.1% vs. 32.0% and 19.8%, p<0.001). In the matched cohorts, no significant differences were found in duration of therapy between the golimumab (259.73 days; 95% CI: 247.20-272.26) and adalimumab (268.75 days; 95% CI: 256.03-281.47) patients or persistence (71.16% [95% CI: 67.73%>74.59%] vs. 73.63% [95% CI: 70.16%>77.10%]). Likewise, there were no significant differences in duration of therapy (267.82 [95% CI: 253.81-281.83] vs. 276.26 days [95% CI: 261.68-290.84]) or persistence (73.38% [95% CI: 69.54-77.22] vs. 75.69% [95% CI: 72.59-78.79]) between the golimumab and etanercept cohorts. Conclusions: The mean treatment persistence among golimumab patients is over 70%, and when matched to patients taking adalimumab or etanercept, both duration of therapy and persistence are numerically equivalent between cohorts. Future research is needed to assess the impact of persistence on clinical and economic outcomes. Disclosure of Interest: N. Tandon Employee of: Janssen Scientific Affairs, LLC, S. Haas Consultant for: Janssen Scientific Affairs, LLC, H. Waters Consultant for: Janssen Scientific Affairs, LLC, W. Olson Employee of: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC, C. Gunnarsson Consultant for: Janssen Scientific Affairs, LLC